SISTEM INFORMASI TENAGA PENDIDIK DAN KEPENDIDIKAN PADA SMA NEGERI 1 KUNINGAN - Muhsin .; Dadi Hamdani; Jony Ledarus (NUANSA INFORMATIKA, 2011)
After evaluating and does research in process of management of education data and kependidikan and reporting processes, still there is difficulty in data input and not effective of data reporting processes, and has not his(its computerized some important parts found on management of educator data and kependidikan. Needs existence of a good computerization system and facilitates work done with minimization of mistake happened and eliminates paper ( paperless ). The Application Of Educator data processing and kependidikan is a system integrating key parts. This system can present data from educator energy data process and does process kependidikan of like management of rank data, sertifikasi, and hour(clock teachs. Process of report that is quickly and accurate for leader and reporting to management indirectly can be done based on period which has been determined by user and also leader.Keyword : Computerization, Paperless, Application